Health Communication in Families Affected by Stunting in Indonesia: A Systematic Literature Review - Babys, Salomon Andreas Mesak; Saleh, Amiruddin; Seminar, Annisa Utami; Khomsan, Ali; Babys , Salomon Andreas Mesak (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Stunting is a health issue that threatens the existence and quality of global human resources. The prevalence of stunting in Indonesia remains high. Communication is a medium for addressing the problem of stunting. This study aims to explore and analyze the forms, strategies, content, and effectiveness of health communication factors for families affected by stunting in Indonesia, as well as the influence and role of family characteristics in the stunting management process. The study used a systematic literature review method. A total of 22 articles were analyzed using the PRISMA protocol. The results show that health communication practices regarding stunting in families are dominated by structured interpersonal communication and group communication approaches that are linear, top-down, and instructive. The effectiveness of this approach is limited to increasing knowledge, while its impact on changing attitudes and behavior is still low. The success of communication is determined by family characteristics, parenting structures, and economic constraints. It is recommended that communication through cultural figures and a dialogical approach are more effective alternatives. Therefore, health communication in addressing stunting requires a differential and contextual strategy that considers the family profile as an active moderator. The implications of this research are the need to design stunting management programs with clear communication protocols, dialogically oriented communicator training, and collaborative message design that is responsive to family realities.